1998
DOI: 10.1001/archinte.158.4.363
|View full text |Cite
|
Sign up to set email alerts
|

What Do Patients Express as Their Preferences in Advance Directives?

Abstract: The overwhelming desire expressed by the patients in the ADs was not to have their lives prolonged if their medical condition were such that treatment would merely delay death. Only a minuscule number of patients, less than 0.7%, wanted everything done to prolong life regardless of the chance for improvement or the cost. Because such a small percentage of patients have ADs, it is recommended that each hospital appoint a committee on ADs to do everything possible to encourage patients to execute an AD. A second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 14 publications
0
23
1
Order By: Relevance
“…2 Patients, with the guidance of physicians and/or social workers, can limit resuscitative measures in the event of a sudden arrest or critical worsening from a previously stable physical condition. This has resulted in a "limited code" phenomenon.…”
Section: Arch Internmentioning
confidence: 99%
“…2 Patients, with the guidance of physicians and/or social workers, can limit resuscitative measures in the event of a sudden arrest or critical worsening from a previously stable physical condition. This has resulted in a "limited code" phenomenon.…”
Section: Arch Internmentioning
confidence: 99%
“…One study showed that the most recurring directive request was ‘not for CPR’ 6. Being free of pain and not prolonging life in the setting of an incurable illness, injury or permanent change in quality of life are also common wishes 7 8. Although interventions have been implemented to increase prevalence and, theoretically, compliance with patients' wishes, such as the ‘Respecting Patient Choices©’ program in some hospitals, the existence of an AD does not guarantee that its conditions will be met 4…”
Section: Introductionmentioning
confidence: 99%
“…Central to this article are a number of unexamined assumptions. Several of these seem worth examining: (1) prior to losing their ability to make decisions, patients should be able to express their wishes about treatment and express them in documents that in the future might be binding on physicians and other health care providers; (2) when it comes to treatment decisions about theoretical situations not actually faced by patients at the time these documents are executed, patients' wishes should remain stable over time and not be changed at the time the situation is actually faced;…”
mentioning
confidence: 99%